752 CARDIOGENIC SHOCK AS THE FIRST PRESENTATION OF ACUTE ANTRACYCLINE CARDIOTOXICITY: A CLINICAL CASE. (15th December 2022) - Conte, Cristina; D´aiello, Alessia; Cribari, Francesco; Buono, Marco Del; Saponara, Gianluigi; Pinnacchio, Gaetano; Antonio Montone, Rocco; Aurigemma, Cristina; Pedicino, Daniela; Liuzzo, Giovanna; Sanna, Tommaso
Abstract: Background: Several therapeutic strategies are available for cancer patients, leading to a longer life expectancy; however, each drug might have different side effects, which increase morbidity and mortality. Cardiovascular diseases are one of the most frequent and dramatic of these side effects, leading to interruption of a potentially lifesaving treatment or hesitating into heart failure. Clinical Case: A 50 year-old female with recent diagnosis of breast cancer presented to our Emergency Department (ED) for asthenia, vomiting and dyspnea. A first dose of epirubicin and cyclophosphamide as neoadjuvant chemotherapy (CT) was administered three days before the onset of symptoms. Screening echocardiogram performed before starting the CT showed normal systolic ejection fraction, normal diastolic function and no valvular disease. At ED admission, the patient presented hypotension, tachycardia, sweating and mental confusion. The ECG showed sinus tachycardia with diffuse ST segment elevation and diffuse low QRS voltages. Echocardiogram proved severe left dysfunction (LVEF 15%) with low cardiac output (LVOT VTI 6 mm) and elevated ventricular filling pressure (E/e' 26). EAB showed severe hyperlactacidemia. The diagnosis of cardiogenic shock was done and high doses of dobutamine and noradrenaline were started. Laboratory values confirmed multiorgan involvement, in absence of any signs of inflammation and infection. The coronary angiography performed revealed normal coronary arteries and elevated left ventricular end-diastolic pressure (LVEDP 29 mmHg). Despite pharmacological therapy, the patient's condition worsened so we proceeded to IMPELLA CP implantation and started methylprednisolone 10 mg/kg for three days with subsequent tapering doses. After 24 hours, we obtained hemodynamic stability and hyperlactacidemia clearance. Unfortunately, myelotoxicity and marked piastrinopenia (until 16 000*10 9 /L) complicated the clinical course; for this reason, we stopped unfractionated Heparin (UHF) and no anticoagulant therapy, other the one in purge solution, was performed. CMR revealed diffuse signal enhancement during the T2w sequences associated with a global enhancement of T2 Mapping values due to general edema, a global intramyocardial strengthening, a significant enhancement of the T1 mapping values and extracellular volume were described at the delayed enhancement sequences. The hemodynamic conditions progressively improved during the hospitalization and the IMPELLA pump was removed. Serial echocardiograms documented an improvement of the ejection fraction and further mild reduction of ventricular filling pressure (E/e' 8) normal right ejection fraction and initial inferior vena cava collapsibility. All the inotropic supports were suspended; we introduced beta-blocker, ACE-inhibitors, subsequently replaced with sacubitril/valsartan, well tolerated. Conclusion: Acute cardiotoxicity with possible life-threatening conditions regardless of the basal cardiovascular risk class is a rare clinical condition, but needs further investigation. Future researches are warranted to determine the molecular mechanisms underlying cardiotoxicity to contain the side effects, maximize the benefit of the oncological therapy and, when necessary, select the best therapeutic option.